Fiqh approach in halal logistic operation - Harun, Hanifah Musa Fathullah; Muflih, Betania Kartika; Ruzulan, Zulaipa; Sahri, Mardhiyyah; Khalid, Mohammad Mahyudin; Mohd Sirajudin, Mohd Dasuqkhi (The Mattingley Publishing Co., Inc., 2020)
Currently, the rapid growth of the global halal industry is encouraging all nations to compete in halal production activities. Generally, halal food integrity revolves around unlawful (haram) issues and the risk of contamination including smell, taste and colour changes of the goods. These issues demand careful adherence by all parties including the suppliers, manufacturers, distributors, retailers, and customers. Needless to say, it involves movement and logistics services. Halal logistics can further be expanded to include halal logistics hub, halal logistics transportation, halal logistics route, and halal logistics management. Due to the progressive development of the halal global industry, there are various halal related issues specifically on the extension of the handling process of the halal related products from farm to fork. Thus, this study attempts to illuminate the issues in the scope of halal logistics and its integrity whereby the consideration of the Islamic principles and its requirements will be analyzed under the purview of Maqasid al-Shariah. It adopts a qualitative research methodology, whereby descriptive and explanatory approaches are used. This study believes Fiqh approach can serve as a benchmark to constitute a sufficient measure to address the issues properly.